SURİYELİ ÖĞRENCİLER İÇİN ATANAN TÜRKÇE ÖĞRETMENLERİNİN AKADEMİK ÖZ YETERLİKLERİ - KARAASLAN, TUBA (Fırat Üniveristesi, 2019)
Yabancı dil öğretimi akademik, toplumsal veya meslekî gelişim amacıyla kişiye ana dili dışında bir dilin öğretilmesi sürecidir. Çalışmamızın amacı, Suriyeli öğrenciler için açılan kamplara atanmış olan Türkçe öğreticilerinin yabancılara Türkçe öğretimi alanındaki akademik öz yeterlik algılarını belirlemektir. Çalışma, nitel türde olgubilimsel (fenomenolojik) desende gerçekleştirilmiştir. Olgubilimsel desen, tamamen yabancı olmadığımız ama derinden de anlayamadığımız olguları araştırmak için kullanılır. İçerik analizinde, içerikle ilgili sonuçlara ulaşma ve örneklemden elde edilen verilerden içerik etkilerini ölçme amaçlanır. Çalışma grubunu, 2018-2019 eğitim-öğretim yılında Diyarbakır'da çalışan 10 Türkçe öğreticisi oluşturmaktadır. Çalışmamızın sonucunda, katılımcı öğretmenlerin yabancılara Türkçe öğretimine dair akademik öz yeterlik algılarının genel olarak yüksek olmadığı belirlenmiştir.

Foreign language teaching is the process of teaching another language different from the mother tongue for academic, social or vocational development. The aim of this study is to determine the academic self-efficacy perceptions about teaching Turkish to foreigners of Turkish teachers who have been assigned to the camps for Syrian students. The study has been carried out in the phenomenological model. Phenomenological model is used to investigate facts of which we are not completely unfamiliar but we do not understand deeply. In content analysis method, it is aimed to reach the results related to the content and to measure the effects of the content from the data obtained from the sample.The study group constitutes of 10 Turkish teachers working in Diyarbakır during the 2018-2019 academic year. As a result of our study, it has determined that the academic self-efficacy perceptions of the participant teachers about teaching Turkish to foreigners have been not generally high. Keywords: Academic self-efficacy, Syrian students, Turkish teachers, Teaching Turkish to foreigners.
Academic self-efficiency of Turkish-language teachers appointed for Syrian students
Keywords: Eğitim ve Öğretim